Correction: A photoexcited halogen-bonded EDA complex of the thiophenolate anion with iodobenzene for C(sp3)–H activation and thiolation. Issue 47 (23rd November 2021) - Li, Tao; Liang, Kangjiang; Tang, Jiaying; Ding, Yuzhen; Tong, Xiaogang; Xia, Chengfeng
Abstract : Correction for 'A photoexcited halogen-bonded EDA complex of the thiophenolate anion with iodobenzene for C(sp 3 )–H activation and thiolation' by Tao Li et al., Chem. Sci., 2021, DOI: ; 10.1039/d1sc03667j .